ANALISIS KEMAMPUAN KEUANGAN DAERAH DALAM MENDUNGKUNG PELAKSANAAN OTONOMI DAERAH DI KABUPATEN NIAS SELATAN - Mas Intan Purba; Titisman Dakhi; Jhon Firman Fau (PARETO : Jurnal Riset Bisnis dan Manajemen, 2025)
The scope of this research is a study of the analysis of regional financial capacity to support the implementation of regional autonomy in South Nias Regency. The purpose of this study is to determine the level of regional financial capacity to support the implementation of regional autonomy in South Nias Regency. The research method used is ratio analysis using the 2011-2017 Budget Realization Report. The results show that the financial capacity of South Nias Regency to support the implementation of regional autonomy from 2011-2017, as seen from the financial independence ratio, is very inadequate to support the implementation of regional autonomy, as it falls below the 10% criterion. The regional financial dependency ratio is very inadequate, as it falls below the 10% criterion. The degree of physical decentralization ratio is very inadequate, as it falls below the 10% criterion. The financial effectiveness ratio is quite effective, as it falls below the 90% criterion. The regional financial efficiency ratio is very inefficient, as it falls above 100%.